Using seasonal temperature difference in underground surrounding rocks to cooling ventilation airflow: A conceptual model and simulation study - Zhu, Shuai; Cheng, Jianwei; Song, Wanting; Borowski, Marek; Zhang, Yongjun; Yu, Baohai; Wang, Yue; Qi, Chang; Tukkaraja, Purushotham; Hua, Gang; Xu, Yonggang; Ghosh, Apurna; et al. (Wiley-Blackwell, 2020)
With the gradual development of deep mining, heat hazard has become an increasingly prominent problem, which poses a great threat to the coal mine production. In order to reduce the heat hazard effectively, it is necessary to investigate the temperature distribution characteristics and regulation of the surrounding rock of the mine tunnels. Based on field measurement data from a Chinese coal mine, the present study probes into the dynamic law of periodic variation of the heat regulation circle (HRC) in surrounding rocks, which is featured by the serious heat hazard, and further reveals the evolution characteristics of the physical range of HRC and the temperature field distribution. By analyzing field data, it can be concluded that a total of five typical distribution models of HRC of surrounding rocks are summarized. Influencing factors concerning thermophysical properties, thermal environment conditions of the stratum, and boundary conditions play important roles and affect the formation of such five models. A mathematical model of heat regulation and energy storage of surrounding rocks in a mine tunnel is proposed. Calculations of air temperature– regulating capability of HRC and evaluating its cooling storage capacity are also demonstrated. Using the HRC in rocks for cooling underground ventilation may be a good and green engineering practice for coal mines.